Synthesis of Chiral 3-Substituted 3-Amino-2-oxindoles through Enantioselective Catalytic Domino and Tandem Reactions - Pellissier, Hélène (Synthesis, 2019)
The goal of this review is to collect the major developments in the catalytic asymmetric synthesis of 3-substituted 3-amino-2-oxindoles through enantioselective catalytic domino and tandem reactions reported since 2011.1 Introduction2 Organocatalyzed Reactions3 Metal-Catalyzed Reactions4 Conclusion
Keywords: asymmetric catalysis; chirality; oxindoles; domino reactions; enantioselectivity; tandem reactions